Systematic Literature Review: Green Marketing and Consumer Behaviour terhadap Purchase Decision - Mahardhika, Dhimas; Suryadi, Nanang (Journal of Economics and Business UBS, 2025)
This study presents a systematic literature review examining the relationship between green marketing and consumer behaviour toward environmentally friendly purchase decisions. The primary objective is to identify the factors influencing green purchase intention and behaviour and to understand how green marketing strategies encourage consumers to choose sustainable products. Analysis of international studies reveals that environmental awareness, consumer knowledge, green brand image, trust in companies, and social influence are dominant factors shaping consumers’ green purchase intentions. Most of the reviewed studies employed quantitative approaches such as Structural Equation Modelling (SEM) and Partial Least Squares (PLS-SEM), grounded in theories like the Theory of Planned Behaviour (TPB) and Behavioural Reasoning Theory (BRT). The findings demonstrate that effective green marketing strategies not only enhance purchase intention but also strengthen long-term brand loyalty and corporate image. However, a persistent gap between intention and actual behaviour—the green gap—is often attributed to high prices, scepticism toward green claims, and limited consumer education. Consequently, companies should implement authentic, transparent, and sustainability-focused green marketing strategies to build consumer trust and promote more environmentally responsible consumption behaviour.